Alcohol - benzene solubles of Mempening (Lithocarpus Spp) according to different portion of tree high and between sapwood and heartwood / Ahmad Suhaimie Md. Noor - Md. Noor, Ahmad Suhaimie (2004)
Mempening or Lithocarpus spp was subjected to chemical analysis involving samples taken at various high and portion. 2 samples from Mempening tree were tested to know the variation of extraneous component in this species. 2 different high are from base and 80% of bole high. Furthermore, samples are also taken in different portion; sapwood and heartwood. The extractives were found to be higher at lower part and in heartwood.